Natural Resources Contracts and Implementation of Oil and Gas Permits in Foreign Companies Related to Article 33 Paragraph 2 and Paragraph 3 of the 1945 Constitution: Literature Review - Arsyad, Ibrahim; Heliaantoro, Heliaantoro (Greenation Research & Yayasan Global Resarch National, 2024)
The purpose of this article is expected to be a useful reference for policymakers, academics, oil and gas companies, and the general public in understanding and managing Indonesia's natural resources more effectively and responsibly. Structured and normative juridical literature review. Relevant scientific articles are selected, identified, and evaluated during the literature review process. The scope of the study was determined using the PICO (population/problem, intervention, comparison) framework, which was used to establish the study boundaries. A number of relevant scientific articles were selected, identified, and reviewed during the literature review. The PICO framework provides a score to set research boundaries. The legal concept of proper management of oil and gas resources can be realized by making strategic changes through a new paradigm to increase the utilization of domestic oil and gas, increase the role and capacity of SOEs in oil and gas management, change the scheme of domestic market obligations and oil and gas export policies, and adjust the oil and gas fund scheme. analysis of natural resource contracts and the implementation of oil and gas permits in foreign companies, related to the provisions of Article 33 Paragraph 2 and Paragraph 3 of the 1945 Constitution. Observing how these practices can optimize benefits for the national economy while considering social justice and environmental sustainability, in line with the spirit of Article 33 Paragraph 2 and Paragraph 3 of the 1945 Constitution which emphasizes the management of natural resources for the prosperity and welfare of the people.